Peran Mahasiswa KKN UINSU terhadap Penguatan Nilai Religius, Pendidikan, Sosial, dan Lingkungan di Desa Tiganderket, Kabupaten Karo - Sokon Saragih; Siti Nurhaliza; Habiburriziq El Ardhy Saragih; Faiz Putra Ramadhan; Farisa Nadhila Siregar (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The Community Service Program (KKN) represents a concrete implementation of the university’s tri dharma, particularly in the area of community service. This study aims to describe the contribution of UINSU students participating in KKN in strengthening religious, educational, social, and environmental values in Tiganderket Village, Karo Regency, North Sumatra. The research employs a descriptive qualitative method with a participatory approach, in which students act not only as observers but also as active participants in various community activities. The results show that the implementation of KKN has had a positive impact on the community through programs such as regular religious gatherings (wirid), teaching in elementary schools, fardhu kifayah training, eco-print workshops, digital literacy and anti-bullying campaigns, environmental activities, and the “Festival Anak Bangsa.” Each activity was designed based on the local community’s potential and aimed at enhancing village independence and welfare. Furthermore, student involvement in social and religious activities has strengthened spiritual values and social solidarity among residents. Overall, the implementation of KKN not only fosters stronger social relationships between students and the community but also serves as a contextual learning platform for students to integrate knowledge, faith, social awareness, and moral responsibility in contributing to sustainable community development.